Antimicrobial and Antibiofilm Activities of Bacterial Strain P-6B from Segara Anakan Against MRSA 2983 - Ari Asnani; Annisa Permata Dinda; Abdi Rahman Nursyamsi; Dwi Utami Anjarwati (Molekul, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) infection has become a worldwide concern due to the increasing MRSA resistance to antibiotics. This condition encourages the continuous exploration of new anti-MRSA compounds. Thus, this study explored the effect of carbon (starch, glucose, sucrose, lactose) and nitrogen (casein, yeast extract, urea, peptone) sources for the fermentation medium to produce antibacterial and antibiofilm compounds from bacterial strain P-6B against MRSA 2983. The results showed that six-day incubation produced bioactive extracts with the highest antimicrobial activity (11.361 ± 0.860 mm) and the highest activity to inhibit biofilm formation (89.159 ± 0.293% %). In comparison, three-day incubation produced a bioactive extract with the highest activity to degrade biofilm (86.450 ± 3.260%). Glucose was the best carbon source to produce an extract with antibacterial and biofilm inhibition activities. However, starch was the best carbon source to produce an extract with biofilm degradation activity. Urea was the best nitrogen source to produce extracts with antimicrobial and antibiofilm activities. Species identification based on the 16S rRNA gene revealed a 99.78% similarity with Ochrobactrum intermedium strain NBRC 15820 (NR_113812.1). These findings suggested the potency of Ochrobactrum P-6B from Segara Anakan Cilacap as indigenous sources of bioactive compounds with anti-MRSA activities.